2016
DOI: 10.1116/1.4944586
|View full text |Cite
|
Sign up to set email alerts
|

Blood compatibility assessment of polymers used in drug eluting stent coatings

Abstract: Differences in thrombosis rates have been observed clinically between different drug eluting stents. Such differences have been attributed to numerous factors, including stent design, injury created by the catheter delivery system, coating application technologies, and the degree of thrombogenicity of the polymer. The relative contributions of these factors are generally unknown. This work focuses on understanding the thrombogenicity of the polymer by examining mechanistic interactions with proteins, human pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…PEVA (poly[ethylene‐co‐vinyl acetate]) and PBMA (poly[ n ‐butyl methacrylate]) were used on SS‐SESs, whereas PVDF‐HFP (poly[vinylidene fluoride‐co‐hexafluoropropylene]) is the polymer used in CoCr‐EESs. The PVDF‐HFP “fluoropolymer” used on CoCr‐EESs adsorbs and retains albumin compared with BMSs, and this is thought to help minimize platelet adhesion and activation and leukocyte recruitment . In a preclinical study, other fluoropolymer‐coated metallic stents, in the absence of antiproliferative drugs, showed significantly less inflammation and less neointima than BMSs at 28 and 90 days in the coronary arteries of pigs .…”
Section: Discussionmentioning
confidence: 99%
“…PEVA (poly[ethylene‐co‐vinyl acetate]) and PBMA (poly[ n ‐butyl methacrylate]) were used on SS‐SESs, whereas PVDF‐HFP (poly[vinylidene fluoride‐co‐hexafluoropropylene]) is the polymer used in CoCr‐EESs. The PVDF‐HFP “fluoropolymer” used on CoCr‐EESs adsorbs and retains albumin compared with BMSs, and this is thought to help minimize platelet adhesion and activation and leukocyte recruitment . In a preclinical study, other fluoropolymer‐coated metallic stents, in the absence of antiproliferative drugs, showed significantly less inflammation and less neointima than BMSs at 28 and 90 days in the coronary arteries of pigs .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the polymer in Xience‐EES was poly( n ‐butyl methacrylate) (PBMA) encapsulated by a poly(vinylidene fluoride‐co‐hexafluoropropylene) (PVDF‐HFP). PVDF‐HFP (used on Xience‐EES) retained more albumin and platelet interaction behavior than PBMA and polystyrene‐ b ‐polyisobutylene‐ b ‐polystyrene (used on Taxus Liberté‐PES) . Thus, the difference in protein and surface materials may be attributed to the different properties in antithrombogenicity between the two DES.…”
Section: Discussionmentioning
confidence: 99%
“…The polymer in DES is a carrier of eluted drug and has several characteristics that improve biocompatibility of the stent through anti-inflammatory and antithrombotic effects. [29][30][31][32] Previous studies demonstrated that polymer coating provides thromboresistance through the modification of surface properties such as electrostatic forces, hydrophilic interaction, and roughness. [33][34][35] In particular, the fluoropolymer in Xience-EES was designed to have better biocompatibility for blood and vascular tissues compared with that in older stents.…”
Section: Thrombogenicity and Stent Characteristicsmentioning
confidence: 99%
“…In this context, the report of Cornelius et al 1 on the interaction of lipoproteins with bare and polyethylene glycol-modified polyurethane surfaces can be highlighted, as well as the two reports pointing to differences in plasma protein adsorption and activation at different surfaces. 2,9 Szott et al 2 and Gupta et al 3 also report differences in platelet activation between different surfaces. The two latter studies contribute to the growing body of evidence that platelet spreading may not be representative of other activation phenomena.…”
mentioning
confidence: 99%